PERLINDUNGAN HUKUM TERHADAP KONSUMEN PADA PEMBELIAN BARANG YANG TIDAK SESUAI DENGAN GAMBAR PADA MARKETPLACE SHOPEE - Gunawan, Angeline; Yor, A. Kasimirus; Sutanto, Very Werson (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
E-commerce transactions, such as those on the Shopee platform, are a legal relationship involving three parties: the consumer, the seller, and the platform (Shopee). This relationship creates liabilities and obligations for each party, which much be adhered to ensure transaction is conducted properly and fairly. To protect consumers, businesses are required to provide accurate and honest information and carry out responsibly. Consumers are also required to exercise caution in transactions and retain proof of transactions to guard against possible order discrepancies. This evidence is expected to sthrengthen the consumer’s position in online buying and transsactions, which are often perceived as weaker than businesses.